Sensitivity of Hydra attenuata and Hydra viridis to diuron and ethoprophos pesticides, Costa Rica - Jones, Caroline; Ugalde, María del Rocío; Jiménez, Katherine; Mena, Freylan; Vargas, Seiling (Uniciencia, 2023)
[Objective] The objective was to determine which of the two hydra species (Hydra attenuata or Hydra viridis) was more sensitive to two pesticides, and then use the most sensitive species as part of the battery of test organisms of the Ecotoxicological Studies Laboratory (ECOTOX). [Methodology] For this purpose, dilutions of two of the most commonly used pesticides in pineapple cultivation in Costa Rica which were detected in water samples were used: the herbicide diuron and the insecticide ethoprophos. Toxicity bioassays were conducted with each of these substances and with a mixture of these substances. The morphological state of the hydras was recorded. In addition, the mean effective concentration (EC50), mean lethal concentration (LC50) and toxicity interactions were evaluated in terms of three possibilities: antagonistic, additive or synergistic. [Results] H. attenuata was the most sensitive species to both pesticides, with an LC50s of 16.84 mg/L and 103.01 mg/L, and an EC50s of 4.24 mg/L and 23.4 mg/L for diuron and ethoprophos, respectively. Furthermore, H. viridis had an LC50s of 36.94 mg/L and 103.01 mg/L, with an EC50s of 13.64 mg/L and 53.12 mg/L, also for diuron and ethoprophos, respectively. Exposure to the pesticide mixture only caused mortality in H. viridis and had a synergistic effect on both species. [Conclusions] These results suggest that H. attenuata is the most appropriate species for the evaluation of pesticide effects, but further studies should be conducted on the interactions of contaminants in mixtures, since these may modify their toxicity for different species.